(untitled) (Acta Scientiarum. Biological Sciences, 2024)
Considering the growth of aquaculture and its potential environmental impacts, this study aimed to evaluate the patterns and trends of research on water quality in fish farms in Brazil, focusing on environmental differences between fishponds and net cages. We conducted a bibliometric survey from the Aquatic Sciences and Fisheries Abstracts (ASFA) and Web of Science databases, using the keywords "fish farm" or "fishpond" and "monitoring" and "water quality". After screening the retrieved documents, a total of 37 original studies were selected. Publication year, locality, pond type, culture characteristics, trophic state index, and values of chemical, physical and biological variables were collected. It was observed an increasing trend in the number of studies over time, with publication peaks in 2014 and 2018. Net cages were evaluated by 60% of the published research, which included between 3 and 750 tanks per study. Fishponds were evaluated by the remaining fraction of the studies, which included from 1 to 50 tanks per study. The five regions of the country were unequally represented: Southeast (54%), Northeast (24%), South (14%), North (5%), and Midwest (3%). Forty-seven distinct variables were recorded, and the most frequent were temperature, dissolved oxygen, and ph. Significant differences were observed in total phosphorus, chlorophyll-a, and orthophosphate concentrations among different pond types, with higher values in fishponds. The findings of our study showed high potential for eutrophication in the aquaculture systems in Brazil and highlighted the urgency for an effective management of this activity in the country. Nevertheless, there is still a lack of information and studies on this topic to support informed decision-making. We also propose some general guidelines.